(untitled) (Ocean and Coastal Research, 2021)
Shrimps are the main fishery resource in marine waters off Sergipe (northeastern Brazil), where they are landed in three categories: ‘espigão’, ‘escolha’ and ‘pistola’. The objective of this study was to identify which species are landed in each category, relating to the perception of stakeholders, and to analyze their effect on the interpretation of historical catch statistics. Samples of 3kg were collected monthly for each category before landing in Aracaju (May/2015-May/2016) to identify the shrimp species caught. All specimens were identified, measured (carapace length - mm) and weighed (total weight - g), and had their sex determined. We interviewed attendees of two meetings promoted by the Programa de Monitoramento Participativo do Desembarque Pesqueiro in Aracaju and Pirambu, the two main ports where shrimp catches are landed in Sergipe, and asked for their perception of shrimp species included in each category. Finally, we used all shrimp catch data available for Sergipe in a national reconstructed database to improve the reconstruction based on the species composition estimated here for the main shrimp species. The analysis of each category indicated the presence of commercially important species (Xiphopenaeus kroyeri, Penaeus subtilis, Penaeus brasiliensis, and Penaeus schmitti), and also species of no local commercial interest: Exhippolysmata oplophoroides, Nematopalaemon schmitti, Rimapenaeus constrictus, and Sicyonia dorsalis. The category ‘espigão’ was dominated by X. kroyeri (94.2%) and ‘escolha’ by P. subtilis (95.3%). ‘pistola’ was mostly P. subtilis (78.3%), almost all of them females, followed by P. schmitti (12.3%). The perception of stakeholders was correct for ‘espigão’ and ‘escolha’, but not for ‘pistola’, as 38% of the respondents classified it as ‘camarãobranco’ (P. schmitti). The mean carapace length for all species together was: 18.90mm (‘espigão’), 22.34mm (‘escolha’), and 30.96mm (‘pistola’). Decreasing catches of X. kroyeri, P. subtilis and P. schmitti in the last years raise concern.